The Effect of Using Two Approaches of Distance Education ( Computer & the Internet) on Students' Achievement at Open Education College and Their Motivation for Learning Mathematics - المدرس الدكتور احمد عبد عون عبد علي (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Distance education is one of the most common educational patterns in our world today, especially in the field of university education, in order to provide higher education opportunities to those who missed these opportunities due to economic and social conditions. The aim of this research is to know the effect of using two methods of distance learning (computer and internet) on achievement and motivation. The research community determines the first grade students in the mathematics department at the Open Education Center (the Open Study Center in Baghdad), which consists of (80) students divided into four study groups. The researcher randomly selected 30 students randomly divided into two experimental groups .a number of educational sites that teach calculus on the Internet has been determined. Acomputer educational program has been prepared, designed and implemented. An achievement test of subjective type was prepared and a measure of motivation for mathematics has been used. The research results in the superiority of the first experimental group that studied using the computer on the second experimental group that studied using the Internet in achievement. There were no statistically significant differences between the two research groups in the motivation measure of learning towards mathematics. The research found that the use of the computer tutorial was better than the Internet in student learning and had a positive impact on their achievement.